Purple Roselle Fortified Yogurt Supplementation Prevents Dioxin-Induced Oxidative Testicular Impairment in Rats - Setianingrum, Ani; Nindhyasari, Shintya; Pratiwi, Herlina; Haskito, Ajeng Erika Prihastuti; Noviatri, Aldila (Graduate School, Universitas Brawijaya, 2024)
Dioxins are highly toxic and hurt multiple organs and systems, including the reproductive organs. This study determined the supplementation of purple roselle (Hibiscus sabdariffa var. altissima) extract into yogurt to prevent testicular deterioration induced by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). The fortification of purple roselle extract into yogurt (RY) was used as a supplement because bioactive components are known to be efficacious in preventing cell damage. Five groups of male Wistar rats were group as follows: 1) negative control (C), 2) TCDD (T), 3) TCDD and 0.5% RY (P1), 4) TCDD and 1% RY (P2), 5) TCDD and 1.5% RY (P3). All treatments were carried out orally for 12 days. Testicular Malondialdehyde (MDA) level and histopathological changes were described quantitatively by one-way ANOVA. The study's results showed that treatment groups P1 (0.5% RY) and P2 (1% RY) had significantly (P<0,05) lower MDA levels than the T group, while group P3 had no significant decrease in MDA level. It proved that supplementation of purple roselle yogurt reduced the formation of MDA in testicular tissue. Histopathology changes show that all groups exposed to TCDD have depleted spermatogenic, Sertoli, and Leydig cells compared to the C group. Suggests that dioxin exposure can have adverse effects on male reproductive organs. This research concludes that supplementing yogurt fortified with purple roselle extract can prevent increased testicular MDA levels. The decrease in testicular cells due to TCDD toxicity was inevitable. However, antioxidant activity from roselle yogurt supplementation can prevent further damage in rat testicular cells. Keywords: Histopathology, MDA, Purple Roselle, Testis, TCDD, Yogurt.